Spain : Financial Sector Assessment Program -Detailed Assessment of the IMF Code of Good Practices on Transparency in Monetary and Financial Policies; Financial Policies. (IMF Staff Country Reports; Country Report, 2006)
An evaluation of observance of good transparency practices relating to banking supervisory and regulatory policy was carried out as part of the Financial Sector Assessment Program (FSAP) against the IMF Code of Good Practices on Transparency in Monetary and Financial Policies. It also provides the evaluation of the National Securities Market Commission (CNMV) relating to securities market supervision, deposit guarantee funds relating to financial policy, and also payment systems oversight conducted as part of the FSAP assessment.